The Role of Islamic and Christian Figures in Implementing the Religious Moderation Value - Putri, Deranni Septianis (UIN Sjech M. Djamil Djambek Bukittinggi, 2023)
This research is motivated by the fact that religious figures play an important role in implementing the value of religious moderation in West Sungai Buluh Nagari. The research aims to determine the role of Islamic and Christian religious figures in implementing the value of religious moderation, supporting factors and obstacles in implementing the value of religious moderation. This research was conducted using qualitative methods. Based on the research results, it can be concluded. First, Religious moderation in Nagari Sungai Buluh Barat can be seen from mutual respect, respect between religious communities, acceptance of local traditions and culture. Second, the role of religious leaders in implementing the value of religious moderation by directing society towards goodness and participating in activities in the community such as mutual cooperation.Third, Supporting factors in implementing the value of religious moderation are the government policy which has designated Nagari Sungai Buluh Barat as a village of religious moderation and community participation in helping each other in building places of worship, while the inhibiting factor in implementing the value of religious moderation is seen in the community's minimal understanding of the value of religious moderation so that giving rise to bad attitudes and not having the means to gather to hold large-scale deliberations.